EFFECT OF THICKNESS AND REACTION MEDIA ON PROPERTIES OF ZNO THIN FILMS BY SILAR - Yergaliuly, Gani; Soltabayev, Baktiyar; Kalybekkyzy, Sandugash; Bakenov, Zhumabay; Mentbayeva, Almagul (Scientific Reports, 2022)
Zinc oxide (ZnO) is one of the most promising metal oxide semiconductor materials, particularly for optical and gas sensing applications. The influence of thickness and solvent on various features of ZnO thin films deposited at ambient temperature and barometric pressure by the sequential ionic layer adsorption and reaction method (SILAR) was carefully studied in this work. Ethanol and distilled water (DW) were alternatively used as a solvent for preparation of ZnO precursor solution. Superficial morphology, crystallite structure, optical and electrical characteristics of the thin films of various thickness are examined applying X-ray diffraction (XRD) system, scanning electron microscopy, the atomic force microscopy, X-ray photoelectron spectroscopy, ultraviolet-visible spectroscopy, photoluminescence spectroscopy, Hall effect measurement analysis and UV response study. XRD analysis confirmed that thin films fabricated using ethanol or DW precursor solvents are hexagonal wurtzite ZnO with a preferred growth orientation (002). Furthermore, it was found that thin films made using ethanol are as highly crystalline as thin films made using DW. ZnO thin films prepared using aqueous solutions possess high optical band gaps. However, films prepared with ethanol solvent have low resistivity (10-2 Ω cm) and high electron mobility (750 cm2/Vs). The ethanol solvent-based SILAR method opens opportunities to synthase high quality ZnO thin films for various potential applications.
Keywords: SILAR; Zinc oxide (ZnO)